Introduction to comparative Heidegger studies: American context - Andriі Karpenko (Cхід, 2016)
The dynamics of Heidegger studies in international intellectual process is the real challenge for the Ukrainian scientific community that makes us look for effective means of generalization and learning context and the content of the problems that have defined the history of the world understanding of M. Heidegger. Comparative studies in the history of philosophy are one of the key areas of research activities that contribute to the identification of semantic coordinates of modern philosophical discourse. American line in reception of Heidegger's philosophy seems to have been based upon the German-French debate on understanding Heidegger, which has nevertheless obtained its own achievements in the reappraisal of the controversial philosopher. Being strongly influenced by the traditional American philosophical trends of pragmatism and analytical philosophy, reception of Heidegger's philosophy has undergone certain transformation of criticism into productive synthesis, which included several paradigmatic shifts. This movement was driven by critique of archetypical Heideggerian motives of poetics of Being and religion of language. The pragmatist and analytical appropriation of Heidegger's concepts and methodologies have been preceded by a long period of postmodernist hermeneutics. The vector of American Heidegger studies should be appropriated to the conditions of the Ukrainian philosophical process, where we have to reinvent the very ground-forming premises in their historical concreteness. The Marxist legacy of the former times should not be negated; it should be reinvented and restored as inherent basis of a novel mind-set.